2015
DOI: 10.4172/2329-9096.1000285
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Kurtkze Expanded Disability Status Scale and the Functional Independence Measure: Measures of Multiple Sclerosis Related Disability

Abstract: This is a summary of an observational study we published in Disability and Rehabilitation in 2003[1], where we compared the Kurtkze expanded disability status scale (EDSS) and the Total functional independence measure (FIM) scale as measures of MSrelated disability. On retrospective electronic charts review of 76 veterans with MS regularly followed in our VA MS clinic, we found the EDSS score to accurately measure MS-related impairment at initial evaluation and on follow-up. However, the EDSS score did not cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
1
Order By: Relevance
“…Although pre-existing dementia can also affect outcome, we did not have sufficient data to measure its influence. Even though FIM scores comprise motor and cognitive components, we nonetheless chose to analyze total FIM scores as we judged that any correlation that we found would be more useful to clinicians and easier to understand [14,16]. LTCI classification [5] also includes items that would be expected to be impaired by dementia such as social interactions, problem solving, memory, and behavioral and psychological symptoms.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pre-existing dementia can also affect outcome, we did not have sufficient data to measure its influence. Even though FIM scores comprise motor and cognitive components, we nonetheless chose to analyze total FIM scores as we judged that any correlation that we found would be more useful to clinicians and easier to understand [14,16]. LTCI classification [5] also includes items that would be expected to be impaired by dementia such as social interactions, problem solving, memory, and behavioral and psychological symptoms.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The Functional Independence Measure (FIM) is a functional assessment scale to assess self-care abilities, monitor the progress of rehabilitation and predict destination at discharge [9][10][11][12][13][14][15][16]. Numerous studies have demonstrated the usefulness and appropriateness of using FIM scores in the assessment of patients after acute stroke [4,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Moreover, most instruments to measure impairments, including EDSS, were developed in persons with mild to moderate MS, and hence the understanding of disease progression in persons in advanced stages or with a more severe disease course is still partial. 310…”
Section: Introductionmentioning
confidence: 99%
“…При сравнении шкал EDSS и TFIM у больных с РС показано, что шкала TFIM является более чувствитель ной для оценки степени инвалидизации, вызванной заболеванием. Она позволяет более оптимально оце нить и динамику функционального состояния паци ента в результате проводимой терапии [27]. По нашему мнению, использование шкалы TFIM у па циентов с заболеванием СОНМ могло бы быть высо коэффективным, особенно при выраженном невро логическом дефиците, когда чувствительность шка 14 лы EDSS заметно снижается.…”
unclassified